rút gọn A= \(\frac{\left(\sqrt{5+3x}-\sqrt{5-3x}\right)\sqrt{5-\sqrt{25-9x^2}}}{x}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(P=\dfrac{x-5\sqrt{x}+2x+10\sqrt{x}-3x-25}{\left(\sqrt{x}+5\right)\left(\sqrt{x}-5\right)}=\dfrac{5\sqrt{x}-25}{\left(\sqrt{x}-5\right)\left(\sqrt{x}+5\right)}=\dfrac{5}{\sqrt{x}+5}\)
\(P=\dfrac{\sqrt{x}}{\sqrt{x}+5}+\dfrac{2\sqrt{x}}{\sqrt{x}-5}-\dfrac{3x+25}{x-25}\\ \Leftrightarrow P=\dfrac{\sqrt{x}\left(\sqrt{x}-5\right)}{\left(\sqrt{x}+5\right)\left(\sqrt{x}-5\right)}+\dfrac{2\sqrt{x}\left(\sqrt{x}+5\right)}{\left(\sqrt{x}+5\right)\left(\sqrt{x}-5\right)}-\dfrac{3x+25}{\left(\sqrt{x}+5\right)}\\ \Leftrightarrow P=\dfrac{x-5\sqrt{x}+2x+10\sqrt{x}-3x-25}{\left(\sqrt{x}+5\right)\left(\sqrt{x}-5\right)}\\ \Leftrightarrow P=\dfrac{5\sqrt{x}-25}{\left(\sqrt{x}+5\right)\left(\sqrt{x}-5\right)}\\ \Leftrightarrow P=\dfrac{5\left(\sqrt{x}-5\right)}{\left(\sqrt{x}+5\right)\left(\sqrt{x}-5\right)}\)
\(\Leftrightarrow P=\dfrac{5}{\sqrt{x}+5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
b)
)\(\sqrt{\frac{4}{\left(2-\sqrt{5}\right)^2}}-\sqrt{\frac{4}{\left(2+\sqrt{5}\right)^2}}\)
= \(\frac{2}{2-\sqrt{5}}-\frac{2}{2+\sqrt{5}}\)
=\(\frac{2\left(2+\sqrt{5}\right)-2\left(2-\sqrt{5}\right)}{\left(2-\sqrt{5}\right)\left(2+\sqrt{5}\right)}\)
=\(\frac{4+2\sqrt{5}-4+2\sqrt{5}}{2^2-\sqrt{5}^2}\)
=\(\frac{4\sqrt{5}}{4-5}\)
=\(\frac{4\sqrt{5}}{-1}\)
\(-4\sqrt{5}\)